IDIOPATHIC PNEUMOMEDIASTINUM – CASE REPORT AND REVIEW OF THE LITERATURE - Iv. Novakov (Trakia Journal of Sciences)
Idiopathic pneumomediastinum is a form of spontaneous pneumomediastinum without predisposing factors and precipitating factors. The purpose of this publication is to present a rare case of this pathological condition. Case presentation: A 21year-old female with spontaneous pneumomediastinum was revealed. Medical history, physical examination, imaging and interventional diagnosis couldn’t determine any predisposing and precipitating factors for pneumomediatinum: case of idiopathic pneumomediastinum with unusual widespread subcutaneous emphysema. Conclusion In conclusion, this publication refers to one relatively rare condition in the thoracic pathology – idiopathic pneumomediastinum. Being a case of idiopathic pneumomediastinum, there was an unusual clinical presentation of widespread subcutaneous emphysema. Despite widespread subcutaneous emphysema, the presenting case confirms the good prognosis of idiopathic pneumomediastinum.